Yi Shen Juan Bi Pill alleviates bone destruction in inflammatory arthritis under postmenopausal conditions by regulating ephrinB2 signaling - Xu, Huihui; Tao, Li; Cao, Jinfeng; Zhang, Peng; Zeng, Hui; Zhao, Hongyan (Frontiers in Pharmacology, 2022)
Yi Shen Juan Bi Pill (YSJB) is a traditional Chinese medicine (TCM) formulation that has a therapeutic effect upon rheumatoid arthritis (RA). However, how YSJB affects bone destruction in arthritis under postmenopausal conditions is not known. We evaluated the therapeutic role of YSJB in bone destruction in postmenopausal arthritis, We used collagen-induced arthritis (CIA) rats who had had been ovariectomized (OVX) as models and explored the possible mechanism from the synovium and bone marrow (BM). Arthritis was generated after ovariectomy or sham surgery for 12 weeks. After 14 days of primary immunization, rats were administered YSJB or estradiol valerate (EV) for 28 days. YSJB could prevent bone destruction in the inflamed joints of rats in the OVX+CIA group. CIA promoted osteoclast differentiation significantly in the synovial membrane according to tartrate resistant acid phosphatase (TRACP) staining, and OVX tended to aggravate the inflammatory reaction of CIA rats according to hematoxylin-and-eosin staining. Immunohistochemistry revealed that the synovium did not have significant changes in erythropoietin-producing hepatocellular interactor (ephrin)B2 or erythropoietin-producing hepatocellular (eph) B4 expression after YSJB treatment, but YSJB treatment reduced nuclear factor of activated T cells (NFATc)1 expression. The BM of rats in the OVX+CIA exhibited remarkable increases in the number of osteoclasts and NFATc1 expression, as well as significantly reduced expression of ephrinB2 and ephB4 compared with the CIA group and sham group. YSJB treatment reduced NFATc1 expression significantly but also increased ephrinB2 expression in the BM markedly. These data suggest that YSJB exhibited a bone-protective effect. YSJB might be a promising therapeutic strategy for alleviating bone destruction in arthritis under postmenopausal conditions, and one of the mechanisms was associated with the modulation of ephrinB2 signaling.